The relationship between nutritional status, severity of diarrhea, and length of stay among pediatric patients with diarrhea in Wangaya Regional General Hospital - Mayland Margaretha Sunata; I Wayan Bikin Suryawan; Anak Agung Made Widiasa (DiscoverSys Inc., 2021)
Background: Diarrhea is a disease still often encountered in society and is one of the biggest causes of death in children. Many factors contributed to the process of diarrhea, including poor nutritional status. According to the data from Riskesdas in 2018, 17.7% of children under five in Indonesia still have nutritional problems. This study was conducted with the aim to know the relationship between nutritional status, the severity of diarrhea and the length of stay among pediatric patients with diarrhea.Methods: This analytical study uses a cross-sectional design, with a total of 87 samples. Pediatric patients in Kaswari room from January 2019 to July 2020 with diarrhea or gastroenteritis, whose body’s length or height, weight and duration of stay listed in the medical record were included in this study, while patients with congenital abnormality like Hirschsprung disease were excluded from this study. The data collected were analyzed using the Fisher test and Chi-square test.Results: Out of 87 children, 49 (56%) of them had normal nutritional status, 78 (87.4%) children had modified vesikari score ? 11, and 68 children had a length of stay < 5 days (78.2%). The results of bivariate analysis between nutritional status and diarrhea severity showed that there was no relationship between the two variables (p = 0.426). The same results were obtained in bivariate analysis between nutritional status and length of stay (p = 0.916).Conclusion: In this study, there was no relationship found between nutritional status, the severity of diarrhea and length of stay among pediatric patients with diarrhea in Wangaya Regional General Hospital.